Incidence of Maternal “Near-Miss” Events in a Tertiary Care Hospital of Central Gujarat, India - Parmar, Niyati T. (J Obstet Gynaecol India, 2016)
BACKGROUND: Constant decline in maternal mortality ratio has given rise to the need of a new indicator. This search has motivated investigation of severe maternal morbidity—“maternal near-miss” (MNM) event. World Health Organization (WHO) defines MNM as “a woman who, being close to death, survives a complication that occurred during pregnancy, delivery or up to 42 days after the end of her pregnancy”. METHODOLOGY: A hospital-based cross-sectional study was carried out at Sir Sayajirao General Hospital (SSGH), a tertiary care referral hospital in Vadodara, Central Gujarat, from May to September 2012. MNM events were identified according to either WHO or Mantel et al. criteria or both. RESULTS: During study period, 1929 live births, 18 maternal deaths and 46 “near-miss” cases were recorded. Among these 46 near-miss cases, 57 near-miss events were identified. Calculated MNM ratio was 23.85/1000 live births, MNM rate was 20.6/1000 obstetric admissions, the ratio of maternal death to MNM event was 1:2.6, and overall Mortality index was 28.1 %. Among near-miss cases, percentage of preterm delivery was 42 % and stillbirth rate was 35 % (16/46). Out of 46 MNM, pregnancies were continued in 3 while 43 pregnancies were terminated. (25 live births, 16 stillbirths, 2 abortions). CONCLUSION: Identification of preventable factors and special preventive actions should be taken for management of complications in such near-miss cases.